From Student to Entrepreneur: How Mentorships and Affect Influence Student Venture Launch. (5th October 2017) - Ahsan, Mujtaba; Zheng, Congcong; DeNoble, Alex; Musteen, Martina
Abstract : Student entrepreneurs face a variety of challenges in building their ventures. In this process, the student founders experience profound changes to their identities as they transition from traditional students to student entrepreneurs. Drawing on the social cognitive theory of self‐regulation and utilizing a partially grounded theory approach we develop a two‐stage process model to elucidate how mentor relationship and student founders affective state impacts entrepreneurial identity and venture progress. Our findings indicate that effective mentoring and positive founder's affect enables students to transition to entrepreneurs. This allows them to assemble resources and take necessary action to move their venture forward. We develop propositions to guide future empirical research in this area.